SOCIO-ECONOMIC DEVELOPMENT OF EU COUNTRIES - Vlad, Camburu (Economics of Agriculture, 2012)
European Unions concern over reducing socio-economic development gaps between member states has been translated into implementation of the following strategies: "Lisabon Strategy" and "Europe 2020 Strategy". The article presents the evolution and the analysis of several chosen indicators, as to reflect the socio-economic development status: life expectancy, development and research gross domestic expenditure, number of persons per household.